A method for preparing gas separation membrane by interfacial polymerization and its application
By introducing a high-gas permeability flux hydrophobic intermediate layer on the surface of traditional ultrafiltration membranes and using an interface polymerization method of 'oil first and water', combined with the use of multi-organic amine containing tertiary amine groups and high-throughput flexible polymers, the traditional The problem of low CO2 permeability and easy damage to the thin-layer separation layer of CO2 separation membranes prepared by the interfacial polymerization method has achieved the preparation and application of high-performance CO2 separation membranes.
Patent Information
- Application Number
- CN202310141030.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-21
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2043-02-21
AI Technical Summary
The CO2 separation membrane prepared by traditional interface polymerization method has low CO2 permeability due to pore seepage phenomenon, and the high-performance thin-layer separation layer is susceptible to compression and scratches during the rolling process of membrane components, resulting in a degradation of performance.
The high-gas permeability flux hydrophobic intermediate layer was introduced on the surface of traditional ultrafiltration membranes, and the interfacial polymerization preparation method was adopted, and a polyorganic amine containing tertiary amine groups was used as the aqueous monomer, and the surface of the separation layer was coated on the surface of the separation layer. Coated with high throughput flexible polymer to protect the separation layer.
It significantly improves the CO2 permeability and separation factor of the CO2 separation membrane, enhances the interlayer bonding force of the membrane, and protects the performance of the thin-layer separation layer during the rolling of the membrane element, ensuring the efficiency and stability of the separation membrane. .
Smart Images

Figure CN116078174B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of polymer membrane preparation, and in particular relates to a method for preparing a CO2 separation composite membrane with high CO2 permeability selectivity by an improved interfacial polymerization method and an application thereof, and is applicable to the field of gas separation membranes. Background Art
[0002] Membrane separation is an emerging technology that uses the difference in the rate at which gas molecules pass through a membrane under the action of a driving force (generally a partial pressure difference) to achieve separation. Compared with other carbon capture methods, membrane separation has the advantages of simple process, great operational flexibility, and no obvious amplification effect, and has broad application prospects. Based on differences in structural characteristics, membranes can be divided into symmetric membranes and asymmetric membranes. Symmetric membranes have high mechanical properties, but large transmission resistance, and the economy of the membrane separation process is poor; while asymmetric membranes with ultra-thin surface structures can independently regulate the structure of each layer, usually with both high selectivity and high permeability, and are the future development direction of separation membranes.
[0003] Interfacial polymerization is a method of generating a dense, continuous polymer separation layer through chemical reactions at the interface of two immiscible phase solutions. Compared with the traditional blade coating method, the interfacial polymerization method involves reaction and diffusion coupling, and the process is complex and difficult to control, but it is easier to obtain a thin and defect-free separation layer, and it is less dependent on the accuracy of the film-making equipment, and has broad application prospects.
[0004] The traditional interfacial polymerization process is to directly use ultrafiltration membrane as the base membrane, small molecule binary organic amine monomers such as piperazine and m-phenylenediamine as the aqueous phase monomer, and trimesoyl chloride as the organic phase monomer. The base membrane is first soaked in the aqueous phase solution, and then reacted at the interface of the two phases in the organic phase solution, that is, the "water first, then oil" method is used to prepare the separation membrane. This membrane preparation method has been widely used in the preparation of nanofiltration membranes and reverse osmosis membranes in industry, but it is difficult to use in the field of gas separation. This is because the primary layer of the membrane prepared by the traditional interfacial polymerization method starts to grow from the membrane pores of the base membrane and eventually forms a thin and dense rigid separation layer. According to the "resistance series model" of gas separation membranes, even if there is a small pore penetration depth in the membrane pores, the resistance of gas permeation through the membrane will increase significantly, resulting in a sharp decrease in the membrane permeation selectivity. At the same time, the cross-linked network formed by the interface reaction of the two-phase monomers used in the traditional interfacial polymerization reaction is extremely rigid, the free volume of the separation layer is small and lacks active groups, and the CO2 permeation selectivity is extremely poor. For example, the CO2 permeability of the membrane prepared by the conventional interfacial polymerization method (see comparative example) using piperazine as the aqueous monomer and trimesoyl chloride as the organic monomer at 25°C and 0.50 MPa of saturated humidity CO2 / N2 (15 / 85 vol%) mixed gas was only 3.7 GPU (1 GPU = 10 -6 cm 3 (STP)cm -2 s -1 cmHg-1 ), the CO2 / N2 separation factor is 31.
[0005] Membrane elements are the basic operating units of membrane separation. Any separation membrane must be prepared into membrane elements before it can be used. In order to reduce concentration polarization and ensure uniform and stable gas flow and sufficient mass transfer in the membrane element, it is usually necessary to fill the membrane bags with diamond-shaped meshes formed by double-layer filaments crossing each other. However, the high-performance thin separation layer is often compressed and scratched by the meshes during the membrane element rolling process, resulting in an irreversible decline in membrane performance and even loss of separation selectivity. Summary of the invention
[0006] The purpose of the present invention is to introduce a high gas permeation flux hydrophobic intermediate layer on the surface of a conventional ultrafiltration membrane, and change the preparation process of the conventional interfacial polymerization method to "the intermediate layer first contacts the organic phase solution, and then reacts at the interface of the two phases of the aqueous phase solution", that is, "oil first, then water" membrane preparation process, so as to solve the problem of low membrane CO2 permeation selectivity caused by the pore permeation phenomenon. At the same time, a polyvalent organic amine containing a tertiary amine group is selected as an aqueous phase monomer, and a surfactant and a film-forming reaction regulator are introduced into the aqueous phase to comprehensively regulate the membrane structure from the aspects of groups, molecules and aggregation states, so that the prepared membrane is suitable for efficient CO2 separation. Furthermore, by coating a high-flux flexible polymer on the surface of the prepared multilayer composite membrane of the high-performance separation layer, the thin layer separation layer is protected.
[0007] The technical solutions adopted by the present invention to achieve the above-mentioned purpose are as follows:
[0008] The present invention provides a novel method for preparing a high-performance CO2 separation membrane by interfacial polymerization, comprising the following steps:
[0009] (1) coating a hydrophobic flexible polymer with a concentration of 0.025 to 0.1 wt % on the surface of an ultrafiltration membrane to form a hydrophobic intermediate layer with a high gas permeation flux, so that its CO2 permeability is ≥ 6000 GPU;
[0010] (2) preparing a polyvalent organic amine, an acid absorbent, a surfactant, a film-forming reaction regulator and water into an aqueous phase solution; or not adding a surfactant to the above solution;
[0011] (3) preparing a binary or polybasic acid chloride and an organic solvent to form an organic phase solution;
[0012] (4) uniformly distributing a monolayer of the organic phase solution prepared in step (3) on the surface of the high gas permeation flux hydrophobic intermediate layer in step (1) and then drying the monolayer, and then uniformly distributing a monolayer of the aqueous phase solution prepared in step (2) on the surface of the intermediate layer treated with the organic phase solution to react, blowing off the residual liquid on the surface and then heat treating to obtain a separation layer;
[0013] (5) A high-flux flexible polymer is coated on the surface of the separation layer to obtain a gas separation membrane.
[0014] Wherein, the hydrophobic flexible polymer in step (1) is polydimethylsiloxane or poly(1(trimethylsilyl)-1-propyne); the ultrafiltration membrane material is polysulfone, polyethersulfone, polyacrylonitrile and a mixture thereof;
[0015] Preferably, the hydrophobic flexible polymer is polydimethylsiloxane;
[0016] Preferably, the coating concentration of the polymer is 0.035 to 0.05 wt %;
[0017] Preferably, the ultrafiltration membrane material is polysulfone.
[0018] The aqueous solution in step (2) comprises 0.05-1.0 wt% of a polyvalent organic amine, 0.2-1.0 wt% of an acid absorbent, 0-0.2 wt% of a surfactant and 0.01-0.5 wt% of a film-forming reaction regulator;
[0019] The polyvalent organic amine described in step (2) is one or more of N'N-bis(3-aminopropyl)methylamine, N-aminoethylpiperazine, N,N-bis(3-aminopropyl)piperazine, N,N-bis[3-(methylamino)propyl]methylamine, and 3,3'-diaminodipropylamine;
[0020] The acid absorbent is sodium carbonate, sodium bicarbonate, sodium hydroxide;
[0021] The surfactant is an anionic surfactant such as sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfate, sodium dodecyl sulfate, etc.;
[0022] The film-forming reaction regulator is an ether-oxygen polymer such as polyvinyl alcohol, polyoxyethylene, polyethylene glycol, etc.; or an amine polymer such as polyvinylamine, polyallylamine, polyethyleneimine, etc.;
[0023] Preferably, the polyvalent organic amine is a mixture of N'N-bis(3-aminopropyl)methylamine and 3,3'-diaminodipropylamine in a mass ratio of 1:1;
[0024] Preferably, the acid absorbent is sodium carbonate;
[0025] Preferably, the surfactant is sodium dodecyl sulfate;
[0026] Preferably, the film-forming reaction regulator is polyoxyethylene.
[0027] Wherein, the organic phase solution in step (3) comprises 0.05-1.0 wt % of dibasic or polybasic acid chloride;
[0028] The binary or polyacyl chloride in step (3) is one or more of isophthaloyl chloride, terephthaloyl chloride, 1,4-cyclohexanediyl chloride, and trimesoyl chloride; the organic solvent is n-pentane, cyclopentane, n-hexane, cyclohexane, n-heptane, cycloheptane, n-octane, isoparaffin Isopar G, etc.;
[0029] Preferably, the dibasic or polybasic acid chloride is trimesoyl chloride;
[0030] Preferably, the organic solvent is cyclohexane.
[0031] The organic phase solution in step (4) is evenly distributed in a single layer on the surface of the high gas permeation flux hydrophobic intermediate layer for a time period of 0.5 to 2 minutes, and the distribution temperature is 10 to 30° C.
[0032] Preferably, the contact time with the organic phase solution is 0.8 to 1.2 min;
[0033] Preferably, the contact temperature with the organic phase solution is 15-22°C.
[0034] Wherein, in the step (4), the reaction time of the aqueous solution on the surface of the intermediate layer treated with the organic solution is 0.4 to 2 minutes, the reaction temperature is 20 to 70°C; the heat treatment temperature is 50 to 90°C; the heat treatment time is 10 to 25 minutes;
[0035] Preferably, the reaction time with the aqueous solution is 0.5 to 0.7 min;
[0036] Preferably, the reaction temperature with the aqueous solution is 40 to 60°C;
[0037] Preferably, the heat treatment temperature is 70-80°C;
[0038] Preferably, the heat treatment time is 12 to 17 minutes.
[0039] Wherein, the high-throughput flexible polymer material in step (5) is polydimethylsiloxane or poly(1(trimethylsilyl)-1-propyne), and the coating concentration of the polymer is 0.02-0.06wt%;
[0040] Preferably, the high-throughput flexible polymer material is polydimethylsiloxane;
[0041] Preferably, the coating concentration of the high-throughput flexible polymer material is 0.03-0.04 wt %.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] The present invention improves the traditional interfacial polymerization film-making method, uses a polyamine containing a tertiary amine group as a water phase monomer, uses an ether oxygen polymer or an amine polymer as a film-forming reaction regulator, and uses an anionic surfactant to accelerate the migration rate of the polyamine and the film-forming reaction regulator to the two-phase interface. At the same time, a protective layer is introduced on the surface of the separation layer to achieve a significant improvement in the CO2 separation performance of the prepared membrane. The CO2 separation performance of the prepared gas separation membrane is tested using a mixed gas of CO2 / N2 (15 / 85 vol%) at saturated humidity. The CO2 permeability at 25°C and 0.50 MPa reaches 491 GPU, and the CO2 / N2 separation factor reaches 42; after a PP material diamond-shaped spacer with a thickness of 28 mil and warp and weft lines woven at 90° is pressed on the membrane surface with a 5 kg weight for 15 minutes, the CO2 permeability of the membrane is 533 GPU, and the CO2 / N2 separation factor reaches 38. The present invention lays a foundation for the large-scale preparation and application of high-performance CO2 separation membranes by interfacial polymerization.
[0044] The advantages of the present invention are:
[0045] First, the present invention adopts a novel interfacial polymerization membrane-making method of "oil first, water later", wherein the organic phase solution first swells the high gas permeation flux hydrophobic middle layer, so that the acyl chloride monomer is embedded in the middle layer. When in contact with the aqueous phase solution, the organic amine monomer is accelerated to diffuse into the high gas permeation flux hydrophobic middle layer under the amphiphilic action of the surfactant, so that the separation membrane grows from the surface of the middle layer to the inner layer, thereby enhancing the interlayer bonding force of the multilayer composite membrane. At the same time, the existence of the middle layer completely solves the porosity problem in the traditional interfacial polymerization membrane-forming process, and makes the permeating gas evenly distributed in the lateral direction to quickly pass through the through-holes of the support layer.
[0046] Secondly, the present invention comprehensively regulates the membrane structure from the aspects of groups, molecules and aggregation states. By using polyamines containing tertiary amine groups as aqueous phase monomers, ether oxygen polymers or amino polymers as film-forming reaction regulators, and anionic surfactants as monomer diffusion aids, ether oxygen groups with strong affinity for CO2 and tertiary amine groups with the function of promoting CO2 transfer in an aqueous environment are successfully introduced into the membrane, thereby reducing the rigidity of the cross-linked network film and increasing the free volume of the separation layer, thereby greatly improving the permeability selectivity of the prepared membrane to CO2.
[0047] Finally, based on interfacial polymerization membrane formation, the present invention introduces a high-flux flexible polymer as a protective layer, thereby reducing the impact of screen pressing and scratching on the performance of thin-layer separation membranes during the membrane element rolling process, and ensuring the structural integrity of the separation membrane in the membrane element. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 Schematic diagram of the interfacial polymerization preparation method for a new high-performance CO2 separation membrane;
[0049] Figure 2 The surface SEM images of the polysulfone ultrafiltration membrane, the high gas permeation flux hydrophobic intermediate layer and the high-performance separation layer;
[0050] Figure 3 The surface and cross-sectional SEM images of the prepared gas separation membrane;
[0051] Figure 4 This is a photo of the actual object of Example 1 after being pressed through a mesh. DETAILED DESCRIPTION
[0052] In order to fully demonstrate the role of the protective layer in the membrane element rolling process, the present invention refers to the industrial membrane element rolling process, and places the diaphragm under a PP material diamond-shaped spacer with a thickness of 28 mil and warp and weft threads woven at 90°. A 5kg weight is placed on the spacer and pressed for 15 minutes to examine the changes in diaphragm performance before and after the pressing treatment.
[0053] The present invention introduces a high gas permeation flux hydrophobic intermediate layer on the surface of a traditional ultrafiltration membrane, and develops an "oil first, water later" interfacial polymerization preparation method that first contacts an organic phase solution and then contacts an aqueous phase solution. Furthermore, by introducing a surfactant and a film-forming reaction regulator into the aqueous phase, and coating a high-flux flexible polymer on the surface of the prepared multilayer composite membrane of the high-performance separation layer, a substantial improvement in the comprehensive performance of the CO2 separation membrane is achieved. The CO2 separation performance of the prepared membrane was tested using a mixed gas of CO2 / N2 (15 / 85 vol%) at 25°C, 0.50 MPa, and saturated humidity. The CO2 permeability can reach 491 GPU, and the CO2 / N2 separation factor can reach 42, which has broad application prospects. The present invention lays a foundation for the large-scale preparation and application of high-performance CO2 separation membrane interfacial polymerization. The present invention is further described below in conjunction with the embodiments:
[0054] Example 1
[0055] (1) Polydimethylsiloxane with a concentration of 0.035 wt% was coated on a polysulfone ultrafiltration membrane to form a high gas permeation flux hydrophobic intermediate layer, whose CO2 permeability was about 9800 GPU;
[0056] (2) using deionized water to prepare an aqueous solution containing 0.05 wt % N'N-bis(3-aminopropyl)methylamine, 0.05 wt % 3,3'-diaminodipropylamine, 0.4 wt % sodium carbonate, 0.05 wt % sodium dodecyl sulfate and 0.05 wt % polyethylene oxide;
[0057] (3) using cyclohexane to prepare an organic phase solution containing 0.1 wt % of trimesoyl chloride;
[0058] (4) uniformly distributing the organic phase solution prepared in step (3) on the surface of the high gas permeation flux hydrophobic intermediate layer in step (1) at a constant temperature of 20° C. for 1.0 min; after drying the residual organic solvent, uniformly distributing the aqueous phase solution prepared in step (2) on the surface of the intermediate layer treated with the organic phase solution at a constant temperature of 50° C. for 0.6 min, and then blowing off the residual liquid on the surface; treating the primary membrane in an oven at a constant temperature of 75° C. for 15 min to obtain a separation layer;
[0059] (5) The surface of the separation layer prepared in step (4) is coated with polydimethylsiloxane at a concentration of 0.03 wt % to obtain a gas separation membrane.
[0060] The CO2 separation performance of the prepared gas separation membrane was tested using a saturated humidity CO2 / N2 (15 / 85 vol%) mixed gas: the CO2 permeability at 25°C and 0.50 MPa reached 491 GPU, and the CO2 / N2 separation factor reached 42; after a 28 mil thick PP diamond mesh woven at 90° was pressed on the membrane surface with a 5 kg weight for 15 minutes, the CO2 permeability of the membrane was 533 GPU, and the CO2 / N2 separation factor reached 38.
[0061] Example 2
[0062] (1) Polydimethylsiloxane with a concentration of 0.075 wt% was coated on a polyacrylonitrile ultrafiltration membrane to form a high gas permeation flux hydrophobic intermediate layer, whose CO2 permeability was about 6100 GPU;
[0063] (2) using deionized water to prepare an aqueous solution containing 1.0 wt % N-aminoethylpiperazine, 1.0 wt % sodium bicarbonate, 0.01 wt % sodium dodecylbenzene sulfonate and 0.5 wt % polyvinyl alcohol;
[0064] (3) preparing an organic phase solution containing 1.0 wt% terephthaloyl chloride using n-heptane;
[0065] (4) distributing the organic phase solution prepared in step (3) uniformly on the surface of the high gas permeation flux hydrophobic intermediate layer in step (1) at a constant temperature of 30° C. for 0.5 min; after drying the residual organic solvent, distributing the aqueous phase solution prepared in step (2) uniformly on the surface of the intermediate layer treated with the organic phase solution, and reacting at a constant temperature of 20° C. for 1.0 min, blowing off the residual liquid on the surface; treating the primary membrane in an oven at a constant temperature of 90° C. for 10 min to obtain a separation layer;
[0066] (5) The surface of the separation layer prepared in step (4) is coated with poly(1(trimethylsilyl)-1-propyne) at a concentration of 0.06 wt % to obtain a gas separation membrane.
[0067] The CO2 separation performance of the prepared gas separation membrane was tested using a saturated humidity CO2 / N2 (15 / 85 vol%) mixed gas: the CO2 permeability at 25°C and 0.50 MPa was 309 GPU, and the CO2 / N2 separation factor was 50; after a 28 mil thick PP diamond mesh woven at 90° was pressed on the membrane surface with a 5 kg weight for 15 minutes, the CO2 permeability of the membrane was 364 GPU, and the CO2 / N2 separation factor was 45.
[0068] Example 3
[0069] (1) coating a poly(1(trimethylsilyl)-1-propyne) with a concentration of 0.025 wt % on a polysulfone-polyethersulfone ultrafiltration membrane to form a high gas permeation flux hydrophobic intermediate layer, whose CO2 permeability is about 11700 GPU;
[0070] (2) using deionized water to prepare an aqueous solution containing 0.05 wt % N,N-bis(3-aminopropyl)piperazine, 0.2 wt % sodium hydroxide, 0.2 wt % sodium dodecyl sulfate and 0.25 wt % polyvinylamine;
[0071] (3) using n-pentane to prepare an organic phase solution containing 0.025 wt% 1,4-cyclohexanediyl chloride and 0.025 wt% trimesoyl chloride; (4) uniformly distributing the organic phase solution prepared in step (3) on the surface of the high gas permeation flux hydrophobic intermediate layer in step (1) at a constant temperature of 10°C for 2.0 min; after blowing away the residual organic solvent, uniformly distributing the aqueous phase solution prepared in step (2) on the surface of the intermediate layer treated with the organic phase solution at a constant temperature of 60°C for 1.5 min, and then blowing away the residual liquid on the surface; treating the primary membrane in an oven at a constant temperature of 65°C for 20 min to obtain a separation layer;
[0072] (5) The surface of the separation layer prepared in step (4) is coated with polydimethylsiloxane at a concentration of 0.02 wt % to obtain a gas separation membrane.
[0073] The CO2 separation performance of the prepared gas separation membrane was tested using a mixture of CO2 / N2 (15 / 85 vol%) at saturated humidity. The CO2 permeability at 25°C and 0.50 MPa reached 533 GPU, and the CO2 / N2 separation factor reached 26. After using a 28 mil thick PP diamond mesh with warp and weft woven at 90° to press the membrane surface with a 5 kg weight for 15 minutes, the CO2 permeability of the membrane was 560 GPU, and the CO2 / N2 separation factor was 23.
[0074] Example 4
[0075] (1) coating a polysulfone ultrafiltration membrane with poly(1(trimethylsilyl)-1-propyne) at a concentration of 0.05 wt% to form a high gas permeation flux hydrophobic intermediate layer, whose CO2 permeability is about 8500 GPU;
[0076] (2) using deionized water to prepare an aqueous phase solution containing 0.25 wt% N'N-bis(3-aminopropyl)methylamine, 0.25 wt% N,N-bis[3-(methylamino)propyl]methylamine, 0.75 wt% sodium bicarbonate, 0.15 wt% sodium dodecylbenzene sulfate and 0.35 wt% polyallylamine; (3) using cyclopentane to prepare an organic phase solution containing 0.5 wt% trimesoyl chloride;
[0077] (4) uniformly distributing the organic phase solution prepared in step (3) on the surface of the high gas permeation flux hydrophobic intermediate layer in step (1) at a constant temperature of 25° C. for 0.8 min; after drying the residual organic solvent, uniformly distributing the aqueous phase solution prepared in step (2) on the surface of the intermediate layer treated with the organic phase solution at a constant temperature of 30° C. for 0.4 min, and then blowing off the residual liquid on the surface; treating the primary membrane in an oven at a constant temperature of 50° C. for 25 min to obtain a separation layer;
[0078] (5) The surface of the separation layer prepared in step (4) is coated with poly(1(trimethylsilyl)-1-propyne) at a concentration of 0.04 wt % to obtain a gas separation membrane.
[0079] The CO2 separation performance of the prepared gas separation membrane was tested using a mixture of CO2 / N2 (15 / 85 vol%) at saturated humidity. The CO2 permeability at 25°C and 0.50 MPa reached 390 GPU, and the CO2 / N2 separation factor reached 33. After pressing the membrane surface with a 5 kg weight for 15 minutes using a 28 mil thick PP diamond mesh with 90° longitude and latitude, the CO2 permeability of the membrane was 464 GPU, and the CO2 / N2 separation factor was 29.
[0080] Example 5
[0081] (1) Poly(1(trimethylsilyl)-1-propyne) with a concentration of 0.055 wt% was coated on a polysulfone ultrafiltration membrane to form a high gas permeation flux hydrophobic intermediate layer, whose CO2 permeability was about 8000 GPU;
[0082] (2) using deionized water to prepare an aqueous solution containing 0.05 wt % N'N-bis(3-aminopropyl)methylamine, 0.15 wt % 3,3'-diaminodipropylamine, 0.6 wt % sodium bicarbonate, 0.02 wt % sodium dodecyl sulfate and 0.1 wt % polyethyleneimine;
[0083] (3) preparing an organic phase solution containing 0.1 wt % terephthaloyl chloride and 0.1 wt % trimesoyl chloride using n-octane;
[0084] (4) uniformly distributing the organic phase solution prepared in step (3) on the surface of the high gas permeation flux hydrophobic intermediate layer in step (1) at a constant temperature of 22° C. for 1.0 min; after drying the residual organic solvent, uniformly distributing the aqueous phase solution prepared in step (2) on the surface of the intermediate layer treated with the organic phase solution at a constant temperature of 40° C. for 1.2 min, and then blowing away the residual liquid on the surface; treating the primary membrane in an oven at a constant temperature of 80° C. for 12 min to obtain a separation layer;
[0085] (5) The surface of the separation layer prepared in step (4) is coated with polydimethylsiloxane at a concentration of 0.035 wt % to obtain a gas separation membrane.
[0086] The CO2 separation performance of the prepared gas separation membrane was tested using a saturated humidity CO2 / N2 (15 / 85 vol%) mixed gas: the CO2 permeability at 25°C and 0.50 MPa reached 498 GPU, and the CO2 / N2 separation factor reached 30; after a 28 mil thick PP diamond mesh woven at 90° was pressed on the membrane surface with a 5 kg weight for 15 minutes, the CO2 permeability of the membrane was 541 GPU, and the CO2 / N2 separation factor was 26.
[0087] Example 6
[0088] (1) Polydimethylsiloxane with a concentration of 0.065 wt% was coated on a polyacrylonitrile ultrafiltration membrane to form a high gas permeation flux hydrophobic intermediate layer, whose CO2 permeability was about 7200 GPU;
[0089] (2) using deionized water to prepare an aqueous solution containing 0.8 wt % 3,3'-diaminodipropylamine, 0.5 wt % sodium bicarbonate and 0.15 wt % polyethylene glycol;
[0090] (3) using cyclopentane to prepare an organic phase solution containing 0.4 wt % of isophthaloyl chloride and 0.4 wt % of terephthaloyl chloride;
[0091] (4) distributing the organic phase solution prepared in step (3) uniformly on the surface of the high gas permeation flux hydrophobic intermediate layer in step (1) at a constant temperature of 15° C. for 1.5 minutes; after drying the residual organic solvent, distributing the aqueous phase solution prepared in step (2) uniformly on the surface of the intermediate layer treated with the organic phase solution at a constant temperature of 70° C. for 2.0 minutes, and then blowing off the residual liquid on the surface; treating the primary membrane in an oven at a constant temperature of 55° C. for 22 minutes to obtain a separation layer;
[0092] (5) The surface of the separation layer prepared in step (4) is coated with polydimethylsiloxane at a concentration of 0.06 wt % to obtain a gas separation membrane.
[0093] The CO2 separation performance of the prepared gas separation membrane was tested using a mixture of CO2 / N2 (15 / 85 vol%) at saturated humidity. The CO2 permeability at 25°C and 0.50 MPa reached 349 GPU, and the CO2 / N2 separation factor reached 27. After a 28 mil thick PP diamond mesh with 90° longitude and latitude was pressed on the membrane surface with a 5 kg weight for 15 minutes, the CO2 permeability of the membrane was 411 GPU, and the CO2 / N2 separation factor was 22.
[0094] Comparative Example
[0095] The comparative example is cited from the journals Journal of Membrane Science, 2021, 618, 118572 and Journal of Materials Chemistry A, 2018, 6, 30-35, and its preparation process is:
[0096] (1) Soaking the porous polysulfone support layer in water for 24 hours;
[0097] (2) soaking the support layer in a 2 wt % m-phenylenediamine aqueous solution for 5 minutes and removing surface droplets;
[0098] (3)Use Prepare a 0.1 wt% solution of trimesoyl chloride, then pour it onto the support layer obtained in step (2), and react at 20° C. for 300 s;
[0099] (4) Use The membrane was washed three times with isopropanol and dried at room temperature for 48 h.
[0100] The prepared membrane was tested under pure gas, the CO2 permeability was only 3.7GPU and the CO2 / N2 separation factor was 31.
[0101] Test data and conclusions
[0102] The CO2 separation performance of the prepared gas separation membrane before and after pressing was tested using a CO2 / N2 (15 / 85 vol%) mixed gas at 25°C, 0.50 MPa and saturated humidity, as shown in Table 2.
[0103] Table 2 CO2 separation performance of different embodiments and comparative examples before and after the screen pressing experiment
[0104]
[0105] Compared with the comparative example, the present invention introduces a high-flux hydrophobic intermediate layer on the surface of the ultrafiltration membrane, adopts a novel interfacial polymerization method of "oil first and water later", uses a polyamine containing a tertiary amine group as a water phase monomer, an anionic surfactant as a monomer diffusion aid, and an ether oxygen polymer or an amine polymer as a film-forming reaction regulator, and successfully realizes the preparation of a high-performance CO2 separation membrane. The performance of the prepared membrane is nearly 132 times higher than that of the membrane prepared in the comparative example in terms of CO2 permeability, and the CO2 / N2 separation factor is increased by 35%.
[0106] This is because: the introduction of a high-flux hydrophobic intermediate layer can prevent the porosity phenomenon in the membrane-forming process and make the permeating gas evenly distributed in the lateral direction so as to quickly pass through the through-pores of the support layer; the polyamine introduces tertiary amine groups in the membrane that can promote the CO2 transfer function, so that the prepared membrane can undergo a specific reversible reaction with CO2 molecules under saturated humidity, thereby greatly promoting the specific dissolution and diffusion of CO2 in the membrane; the film-forming reaction regulator can regulate the degree of cross-linking of the polymer separation layer generated by the interfacial polymerization reaction, increase the free volume of the prepared membrane, and at the same time introduce ether oxygen and primary amine groups with strong affinity for CO2, thereby increasing the solubility of CO2 in the membrane; the hydrophilic part of the anionic surfactant can combine with the positively charged polyamine and ether oxygen / amine polymer, and the lipophilic part is adsorbed on the surface of the organic layer, thereby promoting the diffusion of the aqueous phase monomer and the film-forming reaction regulator to the two-phase interface, increasing the growth rate of the primary layer and the membrane-forming efficiency, and at the same time regulating the polymer density of the prepared membrane.
[0107] As mentioned above, the anionic surfactant plays a role in accelerating the diffusion of the aqueous phase monomer and the film-forming reaction regulator into the organic layer during the film-forming process. The addition of the reagent only affects the CO2 permeability and interfacial polymerization reaction conditions of the prepared film. Example 6 proves that if no surfactant is added to the aqueous phase solution, a higher reaction temperature and a longer reaction time are required during the reaction process to grow a dense and defect-free separation layer.
[0108] Coating a high-flux flexible polymer on the surface of the multilayer composite membrane of the high-performance separation layer can protect the complete membrane structure of the thin-layer separation layer to the greatest extent. After being pressed by the screen, the CO2 selectivity of the prepared membrane is only slightly reduced (the CO2 / N2 separation factor of the prepared membrane in Example 1 is only reduced by 9.5% after the screen is pressed), which proves that the high-flux flexible polymer plays a significant protective role on the separation layer, reduces the impact of scratches, scratches and pressing processes on the performance of the thin-layer separation membrane during the processing and manufacturing of membrane elements, and lays the foundation for the large-scale preparation and application of high-performance CO2 separation membranes by interfacial polymerization.
[0109] The technical solutions disclosed and proposed by the present invention can be realized by those skilled in the art by referring to the contents of this article and appropriately changing the conditions, routes and other links. Although the methods and preparation techniques of the present invention have been described through preferred embodiments, relevant technicians can obviously modify or re-combine the methods and technical routes described herein without departing from the content, spirit and scope of the present invention to realize the final preparation technology. It should be particularly noted that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the spirit, scope and content of the present invention.
Claims
1. A method for preparing an interfacial polymerization gas separation membrane, characterized in that: The following steps are involved: (1) Coating a hydrophobic flexible polymer with a concentration of 0.025-0.1 wt% on the surface of an ultrafiltration membrane to form a hydrophobic intermediate layer with a high gas permeation flux, so that its CO2 permeability is ≥6000 GPU; (2) preparing an aqueous phase solution of polyvalent organic amine, acid absorbent, surfactant, film-forming reaction regulator and water; or not adding surfactant to the above solution; (3) preparing a binary or polybasic acyl chloride and an organic solvent to form an organic phase solution; (4) uniformly distributing a monolayer of the organic phase solution prepared in step (3) on the surface of the high gas permeation flux hydrophobic intermediate layer in step (1) and then drying it, then uniformly distributing a monolayer of the aqueous phase solution prepared in step (2) on the surface of the intermediate layer treated with the organic phase solution to react, blowing off the residual liquid on the surface and then heat treating it to obtain a separation layer; (5) Coating a high-flux flexible polymer on the surface of the separation layer to obtain a gas separation membrane; The hydrophobic flexible polymer is polydimethylsiloxane or poly(1-(trimethylsilyl)-1-propyne); the ultrafiltration membrane material is polysulfone, polyethersulfone, polyacrylonitrile and a mixture thereof; The polyvalent organic amine is one or more of N'N-bis(3-aminopropyl)methylamine, N-aminoethylpiperazine, N,N-bis(3-aminopropyl)piperazine, N,N-bis[3-(methylamino)propyl]methylamine, 3,3'-diaminodipropylamine; the acid absorbent is sodium carbonate, sodium bicarbonate, sodium hydroxide; the surfactant is sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfate, sodium dodecyl sulfate; the film-forming reaction regulator is polyvinyl alcohol, polyoxyethylene, polyethylene glycol ether oxygen polymer or polyvinylamine, polyallylamine, polyethyleneimine; The binary or polybasic acid chloride is one or more of isophthaloyl chloride, terephthaloyl chloride, 1,4-cyclohexanediyl chloride, trimesoyl chloride; the organic solvent is n-pentane, cyclopentane, n-hexane, cyclohexane, n-heptane, cycloheptane, n-octane, isoparaffin Isopar G; The high-throughput flexible polymer material is polydimethylsiloxane or poly (1 (trimethylsilyl) -1-propyne), and the coating concentration of the polymer is 0.02-0.06 wt%.
2. The method according to claim 1, characterized in that: The aqueous phase solution includes 0.05-1.0 wt% of polyvalent organic amine, 0.2-1.0 wt% of acid absorbent, 0-0.2 wt% of surfactant and 0.01-0.5 wt% of film-forming reaction regulator.
3. The method according to claim 1, characterized in that: The organic phase solution includes 0.05-1.0 wt% of a dibasic or polybasic acid chloride.
4. The method according to claim 1, characterized in that: The time for the organic phase solution to be evenly distributed in a monolayer on the surface of the high gas permeation flux hydrophobic intermediate layer is 0.5~2 min, and the distribution temperature is 10~30℃.
5. The method according to claim 1, characterized in that: The reaction time of the aqueous solution on the surface of the intermediate layer treated with the organic solution is 0.4-2 min, the reaction temperature is 20-70°C; the heat treatment temperature is 50-90°C; and the heat treatment time is 10-25 min.
6. The interfacial polymerization gas separation membrane prepared by the method for preparing an interfacial polymerization gas separation membrane according to claim 1 is used for separation of gases containing CO2.
Citation Information
Patent Citations
Membrane for desorbing CO2 from solution containing CO2 and preparation method of membrane
CN104607073A
Separation membrane for treatment of gases containing acidic gas, method for producing same, method for separating acidic gas or methane gas, and method for producing acidic gas or methane gas
CN104797328A